Oxidative damage in Echinochloa crus−galli seeds exposed to Diaporthe sp. (Diaporthales, Ascomycota) fungal extract during germination - Somala, Naphat; Manichart, Nutcha; Laosinwattana, Chamroon; Wichittrakarn, Pattharin; Yoneyama, Kaori; Teerarak, Montinee; Chotsaeng, Nawasit (Frontiers in Agronomy, 2024)
This study investigates the inhibitory effects of Diaporthe sp. isolate EC010 extract on barnyardgrass (Echinochloa crus-galli) seed germination and growth. Application of sequential extraction techniques to Diaporthe sp. mycelium resulted in partial separation of the phytotoxic compounds. The ethyl acetate (EtOAc) fraction most greatly reduced seed germination (81.01%), root length (89.18%), and shoot length (84.74%) compared to the control. Chemical characterization using gas chromatography-mass spectrometry revealed major constituents of linoleic acid, butyl ester (9.69%), hexadecanoic acid (7.99%), and 14-pentadecenoic acid (7.86%). With regard to physiological and biochemical indexes, treated seeds exhibited lower imbibition, significantly decreased α-amylase (EC 3.2.1.1) activity (p<0.05), and increased accumulation of malondialdehyde (85.52%) and hydrogen peroxide (141.10%). Moreover, activity of the antioxidant enzymes superoxide dismutase (EC 1.15.1.1) and guaiacol peroxidase (EC 1.11.1.7) was upregulated (67.24 and 61.62%, respectively), while catalase (EC 1.11.1.6) activity was downregulated (-33.75%). The inference is that an imbalance in ROS levels combined with reduced antioxidant potential drives the gradual accumulation of oxidative damage in seed cells and consequent loss of seed viability. All told, these results confirm the Diaporthe extract to induce oxidative stress and inhibit antioxidant enzymes. This study clearly demonstrates the oxidative damage associated with Diaporthe allelochemicals.